DIAGNOSIS AND MANAGEMENT OF NONCONVULSIVE STATUS EPILEPTICUS (NCSE) - Pramesti, Fathia Annis; Husna, Machlusil; Kurniawan, Shahdevi Nandar; Rahayu, Masruroh (Malang Neurology Journal, 2017)
Status epilepticus is an emergency condition in the field of neurology are often undiagnosed and are associated with high mortality and long-term disability. One type of status epilepticus is nonconvulsive status epilepticus (NCSE) in which the diagnosis of NCSE is very difficult because the clinical manifestations appear is agitation or confusion, nystagmus or bizarre behavior such as lip smacking or take goods in the air.The diagnosis was based on clinical features, especially the mental status or the disrupted of consciousness and the changes in the EEG. Diagnosis of NCSE is an important first step, which can avoid the delay in therapy in order to prevent irreversible brain damage. Treatment is by administering benzodiazepines and antiepileptic drugs, while the prognosis is determined by the etiology and associated with brain damage there.